Analisa Implementasi Akad Istishna pada Produk Pembiayaan KPR Syariah (KPR Indent IB) Bank BTN Syariah - Azhar Taufik; Dina Febriani; Asep Supyadillah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the implementation of the istishna’ contract in the KPR Indent IB home financing product at Bank BTN Syariah (BSN) and to assess its compliance with DSN-MUI Fatwa No. 06/DSN-MUI/IV/2000 concerning Istishna’ Sale and Purchase. The background of this research is based on the increasing public demand for home ownership through sharia-compliant financing schemes that are free from elements of riba (usury) and gharar (uncertainty). This research employs a descriptive qualitative method with a case study approach. Data were collected through observation and interviews with officials of Bank BTN Syariah, Harmoni Branch, Central Jakarta, as well as a partner property developer in the Depok area. The data analysis technique applied the Miles and Huberman model, which includes data collection, data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the istishna’ contract in the KPR Indent IB product fulfills the essential pillars and conditions stipulated in the DSN-MUI Fatwa, particularly in terms of payment provisions, clarity of the contract object specifications, delivery mechanisms, and financing risk management. The margin scheme is determined as fixed or tiered without altering the principal price agreed upon at the inception of the contract, thereby avoiding elements of gharar. Risk management is conducted through warning mechanisms, restructuring measures, collateral execution in cases of default, and the imposition of ta’zir penalties allocated to charitable funds. It can therefore be concluded that the implementation of the istishna’ contract in the KPR Indent IB financing product at Bank BTN Syariah is substantially in accordance with sharia principles and the applicable fatwa regulations in Indonesia.